Dual Residency and the OECD Model Tax Convention: A Normative Analysis of Tie-Breaker Rules in the Indonesian Legal Context - Silalahi, Heriantonius; Han, Steven (Yayasan Sinergi Kawula Muda, 2025)
The rapid digitalization of the global economy and the increasing cross-border mobility of individuals have challenged the effectiveness of traditional residency-based taxation systems. For Indonesia, which relies heavily on domestic revenue, these developments create legal and fiscal tensions between safeguarding its tax base and adhering to international standards. This study addresses a significant research gap in the normative analysis of how OECD Model Tax Convention tie-breaker rules are applied within the Indonesian legal framework to resolve dual residency situations, particularly involving migrant workers and digital nomads. Using a doctrinal legal research approach, the study systematically examines Indonesia’s regulatory framework at three levels: (i) substantive norms under the Income Tax Law, (ii) administrative instruments such as PMK 18/PMK.03/2021, and (iii) technical guidelines such as SE-52/PJ/2021. These are then compared with the residency and tie-breaker provisions of the OECD Model Tax Convention to assess their coherence and effectiveness in providing legal certainty. The findings reveal significant gaps between Indonesia’s domestic regulations and international standards, particularly regarding the interpretation and implementation of tie-breaker rules. These gaps increase the risk of double taxation, double non-taxation, and tax base erosion in dual residency cases. Theoretically, this study enriches the literature by contextualizing the relevance of tie-breaker rules in the era of global mobility and digitalization. Practically, it offers policy recommendations for harmonizing domestic regulations with international instruments, strengthening treaty clauses, and enhancing administrative capacity to better protect Indonesia’s fiscal interests.